Eccentricity paced paleoenvironment evolution and microbial community structure in the Gulf of Mexico during the outgoing Early Eocene Climate Optimum - Wang, Danlei; Schwark, Lorenz; Ruebsam, W.; Holman, Alex; Böttcher, M.E.; Idiz, E.; Coolen, Marco; Grice, Kliti (ELSEVIER, 2022)
Orbital-driven climate fluctuations and associated variations in the carbon cycle over short- and long-term time scales can be recorded in sedimentary archives. Bulk geochemical, biomarker, and stable isotope signatures in sediments deposited at the end of the Early Eocene Climatic Optimum (EECO) recovered from the Chicxulub impact crater in the Gulf of Mexico show a strong relationship with Milankovitch cycles, which play a critical role in controlling climatic and environmental oscillations. Our study represents the first highly spatially-resolved biomarker and bulk geochemical record from the EECO. The bulk δ13Ckerogen data records the Milankovitch eccentricity-paced variability of continental weathering throughout the studied interval. Biomarkers (and indices) indicative of redox conditions [e.g., pristane (Pr)/phytane (Ph) ratios], water column stratification and/or salinity conditions (e.g., Gammacerane Index), photic zone euxinia (e.g., isorenieratane, chlorobactene, and okenane) and those that can differentiate between algal communities such as dinoflagellates (dinosteranes), marine pelagophytes (24-n-propylcholestane), chlorophyte algae (24-iso-propylcholestane), and prasinophytes (C28/C29 sterane ratios) show changes controlled by orbital eccentricity frequencies. In particular, eccentricity maxima were marked by more reducing/salinity stratified water conditions, photic zone euxinic episodes, and higher (relative) abundances of prasinophytes. In contrast, eccentricity minima were marked by more oxic water conditions and an increase in cyanobacterial markers. The δ13C offset observed between phytane and C17–C19 n-alkanes may represent shifts between a predominance of autotrophic vs. heterotrophic communities controlled by orbital eccentricity. The direct response of molecular and isotopic composition of organic matter to orbitally controlled climate change in the early Eocene could be proven here for the first time and may be more prevalent in Paleogene sediments worldwide.